Causes of damage to industrial brick masonry chimneys. (April 2017) - López-Patiño, Gracia; Adam, Jose M.; Verdejo Gimeno, Pedro; Milani, Gabriele
Abstract: From the early 19th to the middle of the 20th century, brick chimneys formed part of the industrial landscape. As technology advanced, factories were abandoned and became absorbed by the cities growing around them but masonry brick chimneys found a new role as part of the historical heritage. A large number of these structures are now protected buildings, which means they have to be maintained in a good state of conservation. Architects and engineers who have to assess the condition or retrofit these structures therefore need to be familiar with the different types of damage that can affect brickwork chimneys, and having access to a classification of the different types of damage they are prone to would be very useful to them. This paper classifies and describes the most common defects found in these structures, compiled after a close inspection of 538 Spanish industrial chimneys. The types of damage were classified according to: a) changes in the materials used in their construction, b) damage caused by repeated actions, c) damage due to extraordinary events, and d) damage caused by living organisms. Highlights: The paper classifies and describes the most common defects found in industrial brickwork chimneys. 538 brickwork chimneys were inspected with the aim of determining their general state of conservation. Most of the chimneys were damaged and suffered from deficient maintenance and conservation. These types of damage were classified according to their origin.